Bioethics and high-tech medicine - Sherrow, Victoria (New York : Twenty-First Century Books, 1996)
Discusses biomedical technologies and their consequences including the ethical dilemmas that arise.
Includes bibliographical references (p. 135-140) and index.
Keywords: Medical ethics -- Juvenile literature; Medical ethics